Investigation of the drying characteristics of microalgae using microwave irradiation - Mayol, Andres Philip (Animo Repository, 2015)
Microalgae is one of the alternative feedstock for biofuel production with the highest yield per land area. However, current method in microalgae drying process requires high energy which accounts to about 60% of the total energy of the biofuel production chain. Moreover, conventional means of drying results to uneven drying of the microalgae with respect to slurry thickness. This study investigated the drying of microalgae (Chlorella vulgaris) using microwave irradiation which offers a faster means of drying while providing even drying patterns across the slurry thickness. In this paper, the experiment used three (3) microwave intensity levels (300W, 600W, and 900W) to 10g, 20g, and 30g of microalgae sample, a total of nine (9) samples. Results showed that 30 W/g is the best microwave intensity level per gram of microalgae to attain the bone dry mass of the microalgae, while intensity level 20W/g is best to meet the requirement of obtaining a maximum 10% moisture content in the sample.